Innovations for community services : 16th International Conference, I4CS 2016, Vienna, Austria, June 27-29, 2016, Revised selected papers /: 16th International Conference, I4CS 2016, Vienna, Austria, June 27-29, 2016, Revised selected papers. (2016) - Unknown
No abstract available